Therapy culture and the production of subjectivity in neoliberalism - Urošević Milan (Filozofija i Društvo)
This article explores the relationship between neoliberalism and the phenomena of “therapy culture”. We define therapy culture as a consequence of the spread of ideas, discourses, and practices from psychology and psychotherapy into various realms of society. Previous studies, drawing from cultural sociology, Marxism, and governmentality theory, have failed to adequately address how therapy culture integrates subjectivity with the institutions of the neoliberal mode of regulation. We begin with a historical overview of therapy culture’s evolution through the twentieth century and its role in neoliberal economic reforms. Our analysis then delves into conceptualizing the neoliberal mode of regulation, emphasizing the role it gives to subjectivity. Finally, we propose a theoretical framework integrating Foucault’s “technologies of the self” and Lacan’s concept of “fantasy” to conceptualize the relationship between neoliberalism and therapy culture. By relying on this framework, we will conclude that therapy culture serves as a governmental technology through which neoliberalism integrates subjectivity into the process of capital accumulation.